Efecto de la evolución de los medios de comunicación de la nueva era virtual en el cantón Quevedo año 2021 - Velasquez Bravo, Paola Dayana (2022)
In recent years, the evolution of the concept of training has been dazzled by the appearance and consolidation of the media. The new virtual era and its implementation on the World Wide Web has facilitated access to all kinds of necessary information, causing a considerable increase in interactivity between people from different locations and countries around the world, providing the opportunity to develop their skills and abilities to teleworking, interaction in access to information, to knowledge. When we discuss the use of the virtual age and the new media used by insurgents, we are really discussing three separate but related factors: technology, systems used influences how technology is used, and systems. All of these are known by anyone who lives in a moderately advanced country or city in the virtual world, thus providing the necessary information so that in turn it has unpredictable and valued content in analyzing the effects of the evolution of the media and the new era. virtual in the Quevedo canton seeing in turn new strategies have been proposed based on the modality of the effects of the virtual era representing advanced strategies that give a more professional content in the media.